Trend of research on small and medium enterprises (SMEs) in developing countries in the last five years: a bibliometric analysis - Rafsanjani, Mohamad Arief; Subroto, Waspodo Tjipto; Sakti, Norida Canda; Irawan, Nico (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
. Small and medium enterprises (SMEs) play a pivotal role in driving economic growth, innovation, and employment creation, especially in developing countries. This study employs a bibliometric approach to analyze trends, themes, and scholarly contributions to SME research in these regions over the past five years (2020–2024). Drawing on 485 publications from the Scopus database, the analysis reveals significant trends in scholarly output, key citation metrics, influential authors, and emerging research topics. The findings indicate a steady growth in scholarly interest, with the highest publication output observed in 2022. Research topics such as entrepreneurship, digital transformation, green innovation, and financial management are prominent, reflecting their critical importance to SME development. Additionally, sustainability and Industry 4.0-related themes are identified as having high citation impact, underscoring their relevance to contemporary challenges and opportunities for SMEs. China, the United Kingdom, and India are the leading contributors to the field, with substantial contributions from emerging economies such as Malaysia and Indonesia. This study contributes to the understanding of SME research dynamics by highlighting key areas of focus, identifying influential contributions, and mapping the global landscape of SME scholarship. By providing insights into recent trends and thematic priorities, the study offers practical implications for policymakers, researchers, and practitioners seeking to enhance the resilience, innovation, and sustainability of SMEs in developing countries. The findings underscore the need for targeted strategies and collaborative efforts to address emerging challenges and foster inclusive economic growth through SME development.